(untitled) (Journal of Medicine, 2012)
Since its introduction in 1977, Percutaneous Coronary Intervention (PCI) i.e. coronary angioplasty and/or stenting have gained increasing importance in the treatment of coronary artery disease. PCI has reduced the need for coronary artery bypass graft (CABG) surgery and are performed more and more frequently worldwide including Bangladesh. Though Dhaka Medical College Hospital (DMCH) is the pioneer institute for medical education in this country, the facilities for PCI and other cardiac intervention were previously not available in this institute. Recently, however, PCI has been introduced in DMCH. We are here reporting the first regular successful case of PCI done in DMCH. DOI: http://dx.doi.org/10.3329/jom.v13i1.10046 JOM 2012; 13(1): 43-45